Harnessing Autosuggestion Techniques to Manage Hypertension in the Elderly: A Novel Intervention for Improved Health Outcomes and Quality of Life - Wahidin Wahidin; Heny Setyawati; Sofwan Indarjo; Dina Nur Anggraini Ningrum (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Background: Hypertension is a significant health problem among the elderly population, with an estimated prevalence ranging from 60% to 80%. Proper treatment of hypertension in the elderly is essential, as it can lead to decreased quality of life, difficulties in social and physical functioning, and an increased risk of cardiovascular and cerebrovascular diseases. Objective: This study explores the potential use of autosuggestive techniques as a new intervention in managing hypertension in the elderly to improve health outcomes and quality of life. Method: The method used is bibliometric analysis to map and synthesize related literature in the Scopus reputable database. Key Results: The main results of the analysis show that managing hypertension in the elderly requires a comprehensive approach, including knowledge, attitudes, and practice (KAP) intervention models, family support, and the development of self-empowerment models. Autosuggestive techniques have the potential to be integrated into this approach as a novel intervention that can improve blood pressure control and quality of life in older people with hypertension. Conclusion: This study concludes that autosuggestive techniques can be a promising intervention to improve health outcomes and quality of life in the elderly with hypertension. Integrating these techniques into a comprehensive hypertension management approach can provide significant benefits to the elderly population.